Nepal’s Foreign Policy: Challenges and Prospects (Shanti Journal, 2023)
Nepal has undergone tremendous changes since it became republic in 2008. With the promulgation of the new Constitution drafted by the elected people’s representatives in 2015, Nepal has continued to engage with nations beyond India and China. This paper focuses on the foreign policy behavior and strategy of small states in the international system. Further, it explains the behavior and strategies employed by those states by examining several concepts and historic facts and applying them in the context of Nepal. The article states that geo-strategic situation and non-alignment stance of nepal that try to maintain and extend bilateral relations with the immediate neighbors and other actors in the international system, and further integrates them into regional and international frameworks to secure its survival.